UTERINE SCAR IS A RISK FACTOR FOR PLACENTA PREVIA. A CASE CONTROL STUDY - Akhtar, Naheed; Samad, Ambreen; Naz, Talat (Khyber Journal of Medical Sciences, 2023)
OBJECTIVE: Uterine scar is a risk factor for placenta previa. A case control study MATERIAL AND METHODS: The study was conducted in Gynae A Unit of Khyber Teaching Hospital Peshawar from June 2021 to November 2021. Sample size 81 was used according to Kelsey sampling formula. Patients were divided into 2 groups. Group A includes 27 patients with placenta previa as cases and group B includes 54 patients admitted as control. An informed consent was taken from the patients. Secondary risk factors like age, parity, miscarriages, uterine curettage, smoking, history of myomectomy, previous cesarean sections and previous history of placenta previa were also evaluated. Other causes of antepartum hemorrhage like placental abruption and bleeding due to local causes and unclassified APH were excluded from the study. RESULTS: A total of 2467 patients were delivered during the study period. Among them 27 presented as cases of placenta previa and 54 were taken as control with case to control ratio of 1:2. Most common risk factor leading to placenta previa was advanced maternal age > 35 years (OR= 5.2, P-value 0.001) followed by previous cesarean section (OR= 2.96, P-value 0.026), history of curettage (OR= 2.29, Pvalue 0.095) and history of miscarriage (OR= 2.21 P-value 0.005). CONCLUSION: Uterine scar is a risk factor for placenta previa.